Emerging therapeutic potential of whey proteins and peptides - YALÇIN, AHMET SUHA (BENTHAM SCIENCE PUBL LTD, 2006)
Whey is a natural by-product of cheese making process. Bovine milk has about 3.5% protein, 80% of which are caseins and the remaining 20% are whey proteins. Whey proteins contain all the essential amino acids and have the highest protein quality rating among other proteins. Advances in processing technologies have led to the industrial production of different products with varying protein contents from liquid whey. These products have different biological activities and functional properties. Also recent advances in processing technologies have expanded the commercial use of whey proteins and their products. As a result, whey proteins are used as common ingredients in various products including infant formulas, specialized enteral and clinical protein supplements, sports nutrition products, products specific to weight management and mood control. This brief review intends to focus on scientific evidence and recent findings related to the therapeutic potential of whey proteins and peptides.
Keywords: proteins; alpha-lactalbumin; beta-lactoglobulin; immunoglobulin; lactoferrin; bioactive peptide; PLASMA GLUTATHIONE LEVELS; MILK-PROTEINS; BIOACTIVE PEPTIDES; LACTOFERRIN; ANTIBACTERIAL; INCREASES; SUPPLEMENTATION; LACTOPEROXIDASE; OPPORTUNITIES; MODULATION